When the Eel Meets Dams: Larger Dams’ Long-Term Impacts on Anguilla anguilla (L., 1758) - Podda, Cinzia; Palmas, Francesco; Pusceddu, Antonio; Sabatini, Andrea (Frontiers in Environmental Science, 2022)
Diadromous fish, like the European eel Anguilla anguilla (L., 1758), are highly threatened by dams that disrupt the river connectivity, consequently impeding fish movements to reach feeding and spawning habitats. In this study, variation in eel occurrence between a historical period (1940-1970) and a most recent one (2016-2020) was assessed throughout the Sardinian rivers’ network (more than 450 sites). Using Boosted Regression Trees (BRT) we investigated relationships between eels’ occurrence and a set of spatial and temporal environmental variables including a set of dams’ construction features for each period. An overall decrease by 65% of eels’ occurrence was noticed during the ca. 80-years period under scrutiny. Considering a subset (105 sites for the historical period and 88 for the recent) characterized by the presence of larger dams (height >15 m), eels’ occurrence dropped by 85%. In dam-free sites or in sites without downstream dams, eel’s occurrence dropped by ca. 44%. During the historical period, eels’ occurrence was mostly affected by time since the initial habitat fragmentation, flow, distance to dam, connectivity, and dams’ height. In the most recent period, eels’ occurrence is mostly affected by dams building year, dam-to-sea distance, and, again, dams height. Results pinpoint that dams’ construction features and the time from their construction have significant negative effect on eels’ occurrence. Addition of future effective eels’ restoration practices, apart any other adverse environmental stressor, must consider dams’ removal, wherever socially sustainable, or the modification of construction features of dams (like excessive height) with the most adverse effects on eels’ distribution and addition of fish ladders.